Hans Scharoun's 'dwelling cells' and the autonomy of architecture - Borsi, Katharina (Taylor & Francis, 2018)
The paper argues that Hans Scharoun’s articulation of the Siedlung Siemensstadt (1929 – 1931) and Charlottenburg Nord (1956 – 1961) exemplify a process of typological reasoning about how to house and group the urban population, hyperarticulating the spatial needs of the modern domestic family and its correlative of the neighbourhood, helping to mobilise the aspirations of the autonomous individual targeted by liberal government. This account does not support the insistence on modernism’s break with the past as the canon of architectural histories suggest. Instead, it demonstrates a continuity of spatial reasoning about the socio political concept of the family and the neighbourhood as established at the beginning of the twentieth century, taken up by architectural modernism’s impetus for experimentation. Conversely, the strategic value of typology is not seen as simply providing a spatial field of social intervention as the recent literature on urban governmentality suggests. Instead, it is typology’s particular formal and organisational specificity that allows its alignment with defined governmental strategies, continually problematizing the space and the government of the urban population.